2003
DOI: 10.1046/j.1365-2036.2003.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Sandostatin LAR (long‐acting octreotide acetate) for malignant carcinoid syndrome: a 3‐year experience

Abstract: SUMMARYBackground: Somatostatin analogues are the best therapy for controlling the symptoms of malignant carcinoid syndrome. Octreotide acetate given as subcutaneous injection up to three times daily, intramuscular Lanreotide injection given once per 1-2 weeks and monthly intramuscular Sandostatin LAR have demonstrated similar efficacy in short-term studies. Aim: To assess the long-term effect of Sandostatin LAR on the management of patients with malignant carcinoid syndrome. Methods: This was a 3-year retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 28 publications
2
43
0
3
Order By: Relevance
“…The long-acting analogs of somatostatin, lanreotide (Somatuline ® ; Beaufour Ipsen Pharma, Paris, France) and octreotide (Sandostatin ® ; Novartis, Basel, Switzerland), have been shown to be effective in relieving flushing and diarrhea associated with carcinoid syndrome [6,7,8,9]. Indirect data also suggest that somatostatin analogs may have a beneficial effect on patient survival [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-acting analogs of somatostatin, lanreotide (Somatuline ® ; Beaufour Ipsen Pharma, Paris, France) and octreotide (Sandostatin ® ; Novartis, Basel, Switzerland), have been shown to be effective in relieving flushing and diarrhea associated with carcinoid syndrome [6,7,8,9]. Indirect data also suggest that somatostatin analogs may have a beneficial effect on patient survival [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect data also suggest that somatostatin analogs may have a beneficial effect on patient survival [3]. Different formulations of these somatostatin analogs are available and, although all seem to be safe and effective, comparative studies in patients with carcinoid syndrome have shown that lanreotide, 30 mg given every 10 days [8], or octreotide, given every 4 weeks [9], are preferred to octreotide given 2–4 times/day. These findings suggest that prolonged-release (PR) formulations are more appropriate for the long-term treatment of the majority of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The crisis may occur independently, during infection, or as a result of medical procedures: general anaesthesia, endoscopy, tumour biopsy, surgery, embolisation, radioisotope therapy or chemotherapy. Therefore, it is recommended to use somatostatin analogues in the pre-operative period or during surgery on NENs patients [25][26][27].…”
Section: Symptoms Of the Hormonally Active Nens Of The Small Intestinmentioning
confidence: 99%
“…The leading biotherapy method is treatment with SSA (lanreotide and octreotide), which are indicated for the symptomatic therapy of hormonally active NENs of the small intestine. SSA are the preferred treatment option for carcinoid crisis [18,25]. There are ongoing clinical studies on the use of new SSA (pasireotide) in cases of resistance to the standard treatment of carcinoid syndrome [66].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…and deep s.c. routes every 28 days. Biochemical response rates with an inhibition of hormone production are seen in 30-70% with symptom control in the majority of patients (Tomassetti et al 1998, 2000, Ricci et al 2000b, Garland et al 2003, Bajetta et al 2006, Toumpanakis et al 2009). Escalation of dose is often required over time for symptom control due to poorly understood 'tachyphylaxis'.…”
Section: Biotherapy Somatostatin Analoguesmentioning
confidence: 99%